Chemical Methods for Cleaning Skin Products Produced from Cattle of the Fergana Valley (Eurasian Scientific Herald, 2022)
Everyone knows about the value of genuine leather. This is an expensive material, resistant to moisture, having an attractive appearance, pleasant to the body. Mankind cannot do without such material as leather. But the choice is complicated by a huge range of skins, and the dressing method is of great importance. It affects not only the price of raw materials, but also its operational characteristics